2016
DOI: 10.21809/rilemtechlett.2016.8
|View full text |Cite
|
Sign up to set email alerts
|

Advances in near-neutral salts activation of blast furnace slags

Abstract: The utilisation of near-neutral salts as activators to produce alkali-activated slag cements offers several technical advantages, including reduced alkalinity of the binders, minimising the risk associated with handling of highly alkaline materials, and better workability of the fresh paste compared to that of sodium silicate-activated slag cements. Despite these evident advantages, the delayed setting and slow early-age mechanical strength development of these cements have limited their adoption and commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…For activation of high-calcium precursors such as blast furnace slags, or for production of hybrid cements with a significant Portland cement content, Na2CO3 and Na2SO4 can also be effective [6,10]. Some definitions of alkali-activation also include MgO, CaO and/or Ca(OH)2 as potential activator compounds.…”
Section: Technology Presentation 21 Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For activation of high-calcium precursors such as blast furnace slags, or for production of hybrid cements with a significant Portland cement content, Na2CO3 and Na2SO4 can also be effective [6,10]. Some definitions of alkali-activation also include MgO, CaO and/or Ca(OH)2 as potential activator compounds.…”
Section: Technology Presentation 21 Descriptionmentioning
confidence: 99%
“…Each precursor will need the correct activator (or combination of activators) to be identified, specified and sourced. There is currently little systematic or predictive information available regarding methodologies or heuristic procedures by which activators can be optimally matched to precursors, so this is currently achieved largely through parametric testing, but the need for improvements in this area has been identified [10].…”
Section: Introductionmentioning
confidence: 99%
“…When a slag with a high MgO content is used, the secondary reaction products can be: hydrotalcite if activated by waterglass [14]; calcite, gaylussite and hydrotalcite when activated by sodium carbonate [15]; ettringite and monosulfoaluminate or no crystalline structures (depending on the Al 2 O 3 content) if activated by sodium sulfate [16]. On the other hand, it is also known that the mechanical properties of AAS are highly depending on the applied activators when using the same solid precursors, exhibiting generally an order of Na 2-SiO 3 [ Na 2 CO 3 [ Na 2 SO 4 [ NaOH at the same curing regimes and ages [17].…”
Section: Introductionmentioning
confidence: 99%
“…Mobasher et al [27] evaluated the structure of an alkali sulfate activated slag cement, and found that ettringite, C-A-S-H, and a hydrotalcite-like MgAl layered double hydroxide (LDH) are the main reaction products. However, Bernal [16] also mentioned that the secondary reaction products are highly depending on the content of MgO and Al 2 O 3 . A high content of MgO and/or low content of Al 2 O 3 favors the formation of poorly crystalline LDHs and AFm type phases, while a reversed condition leads to the generation of monosulfoaluminate and ettringite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation